Understanding mobility characteristics and needs of older persons in urban Pakistan with respect to use of public transport and self-driving. (January 2019) - Ahmad, Zaheer; Batool, Zahara; Starkey, Paul
Abstract: Since 1990, Pakistan's demographic transition has been increasing life spans with a steady rise in the number of older persons. Pakistan faces many challenges in caring for its older population. The proportion of the population aged 60 years and above is estimated to increase from 5.8% in 2000 to 12.4% in 2050. A study was conducted to understand the existing mobility characteristics of the elderly, their perceived needs and constraining factors. Data was collected using convenient sampling from 450 people aged 60 years or older in nine towns within Lahore City. Older people were approached around urban facilities (shops, banks, terminals) and asked to respond to survey questions. Within-residence interviews were also conducted, mainly for those women who declined interviews in public places. Descriptive and comparative analyses were performed, including Pearson's chi squared test for independence. The results are discussed in terms of mode choice, public transport preferences, self-driving issues and the relative benefits of formal and informal public transport options. The study found lower levels of weekly trip-making compared to those reported for older people in China, South Korea and USA. Vehicle ownership (mainly cars and motorcycles) and socio-demographic factors were found to significantly affect trip making. There were large gender differences in trip making and vehicle ownership, suggesting further research and policy action targeting the mobility needs of elderly women. Older persons were concerned about safety issues concerning public transport and self-driving, and also the behavior of transport crews, and this has informed several of the concluding policy recommendations. Highlights: Trip making is significantly different with respect to gender, age, income and vehicle possession. Elderly females are far less mobile; those self-driving is lesser than 1%. Stress-factors affected use of personal vehicles including physical or mental fatigue and fear of being robbed. Elderly are concerned about safety issues concerning public transport, self-driving and behavior of transport crews The preferred modes of travel are car, motorcycle and walking.